PERBEDAAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DI SMA NEGERI 1 PRAFI PAPUA BARAT - Wiska Baharuddin (LP4MK STKIP PGRI Lubuklinggau, 2022)
The research aims to discover,(1) the learning result of the students who were taught by using guided inquairy learning model at SMAN 1 Prafi Papua Barat, (2) the learning result of the students who were taught by using discovery learning model at SMAN 1 in Prafi Papua Barat, (3) the difference of learning result of the students who were taught by using guided inquairy learning model and discovery learning model at SMAN Prafi Papua Barat. The research is quasi experiment. The populations of the research were all of the students in class XI IPA of the second semester at SMAN 1 in Prafi Papua Barat of academic year 2018/2019. The samples were taken by using random sampling technique by choosing two classes from four class of class XI IPA. The two classes were class XI IPA-2 taught by using discovery learning model with 27 students and class XI IPA-3 taught by using guided inquairy learning model with 23 students. The results of the research reveal that (1) Biology learning result of the students who were taught by using discovery learning model at SMAN 1 in Prafi Papua Barat is in very good category, (2) Biology learning result of the students who were taught by using guided inquiry learning model at SMAN 1 in Prafi Papua Barat is in very good category, (3) there is no difference of learning result between the students who were taught by using discovery learning model and guided inquiry learning model at SMAN 1 in Prafi Papua Barat.